Standard and contrast-enhanced doppler sonography in assessment of the vascular pattern in hepatocellular carcinoma - Genadieva-Dimitrova M; Serafimoski V; Popova R; Joksimovic N; Trajkovska M; Caloska V; Todorovska B; Andreevski V; Stardelova K; Isahi U; Curakova E; Stavric S; et al. (My University, 2012)
AIM: Analysis of the type of vascularity in hepatocellular carcinoma (HCC) with various Doppler techniques and evaluation of the possibility of differentiating hepatocellular carcinoma in relation to the vascular pattern from other focal liver lesions. MATERIAL AND METHODS: Standard and contrast enhanced color and power Doppler using contrast medium Levovist was performed in 34 cases of subsequently histopathologically proven hepatocellular carcinoma. The type of vascular pattern was assessed according to the classification of Tanaka and Kubbota. Doppler characteristics of different Doppler methods aimed to allow sonographic diagnosis in different liver lesions. RESULTS: Highly significant difference (p <0.01) was established in vascular patterns between Doppler methods in the analysis of HCC lesions. Power Doppler and contrast-enhanced Doppler methods were superior to color Doppler in detection of the vascular pattern in HCC. Contrast-enhanced power Doppler was superior to standard. With standard and contrast-enhanced Doppler analysis of HCC lesions dominating vascular patterns were: basket pattern (BP), vessel in tumor (VT) and BP + VT. Crostabulation with Wilcoxon test showd highly statistically significant differences (p <0.01) in the sonographically diagnosed HCC lesions between standard and contrast-enhanced color and power Doppler. The difference between sonographical diagnoses in contrast-enhanced color and power Doppler was statistically significant (p <0.05), while in the other comparisons between different methods the difference was not statistically significant (p> 0.05). CONCLUSION: Doppler methods (standard and contrast-enhanced) are useful, safe, easyly applicable modalities for assessing the type and degree of vascularity in hepatocellular carcinoma, and contrast-enhanced Doppler techniques show higher diagnostic value in differentiation of HCC lesions.
Стандардната и контрастно-засилената доплер сонографија во проценката на васкуларниот приказ кај хепатоцелуларниот карцином